Working with What They Have: Professional Development as a Reform Strategy in Rural Schools - Nathan Barret; Joshua Cowen; Eugenia Toma; Suzane Troske (Journal of Research in Rural Education, 2015)
In-service teacher professional development has been used to improve teacher effectiveness. In Kentucky, the National Science Foundation funded a large professional development program called the Appalachian Math and Science Partnership (AMSP) to provide content-based professional development to teachers in rural schools. We show that students assigned to AMSP teachers at a baseline year realized signifi cant math gains not only in that year of assignment but in the following year as well. No gains are evident two and three years after being assigned to AMSP teachers. We frame both the program and its results in the context of teaching careers in rural schools, arguing that limited access to outside labor markets implies that successful professional development may be a key component of improving education in rural locales.